1994
DOI: 10.3168/jds.s0022-0302(94)77225-8
|View full text |Cite
|
Sign up to set email alerts
|

Growth and Viability of Bifidobacterium bifidum in Cheddar Cheese

Abstract: Bifidobacterium bifidum (ATCC 15696) was grown in MRS broth containing cysteine.HCl at 37 degrees C, and the cells were harvested by centrifuging at 1300 x g for 15 min at 4 degrees C. Equal volumes of the cell slurry and a 2.5% solution of kappa-carrageenan were mixed and transferred by drops into a solution of .3 M KCl at 20 degrees C under an atmosphere of nitrogen. The gelled beads were separated, frozen, and lyophilized immediately. This preparation and a commercial powder preparation were added to Chedda… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

14
143
0
9

Year Published

2006
2006
2015
2015

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 213 publications
(166 citation statements)
references
References 10 publications
14
143
0
9
Order By: Relevance
“…Similar results were also noted in semi-hard cheeses supplemented with L. acidophilus and L. paracasei (Bergamini et al, 2006). This same feature for primary proteolysis was also found in previous studies of cheddar cheese supplemented with Bifidobacterium bifidum and L. paracasei (Dinakar and Mistry, 1994;Gardiner et al, 1998), Gouda cheeses with Bifidobacterium spp. and L. acidophilus (Gomes et al, 1995) and goat cheeses with B. lactis and L. acidophilus .…”
Section: Resultssupporting
confidence: 85%
“…Similar results were also noted in semi-hard cheeses supplemented with L. acidophilus and L. paracasei (Bergamini et al, 2006). This same feature for primary proteolysis was also found in previous studies of cheddar cheese supplemented with Bifidobacterium bifidum and L. paracasei (Dinakar and Mistry, 1994;Gardiner et al, 1998), Gouda cheeses with Bifidobacterium spp. and L. acidophilus (Gomes et al, 1995) and goat cheeses with B. lactis and L. acidophilus .…”
Section: Resultssupporting
confidence: 85%
“…Many investigations indicate that addition of probiotic bacteria to cheese in a suitable culture composition and formulation does not significantly or considerably change the flavor and/or other sensory characteristics of the final product compared to the control. It has been reported that bifidobacteria added to cheddar cheese did not exhibit vigorous metabolic activity and did not affect the flavor, texture, or appearance through 24 wk of storage (Dinakar and Mistry 1994). Cheeses with bifidobacteria had higher concentrations of acetic and lactic acids compared to the control (Ong and others 2007), but the sensory differences were unimportant; indicating that bifidobacteria did not exhibit extensive metabolic activity (Gobbetti and others 1997).…”
Section: Effects Of Probiotic Microorganisms On Sensory Acceptance Ofmentioning
confidence: 97%
“…probiotics in the stomach (Gardiner and others 1999). Many researchers and manufacturers have incorporated probiotic bacteria in different types of cheese, such as cheddar (Dinakar and Mistry 1994;Gardiner and others 1998;McBrearty and others 2001), Gouda (Gomes and others 1998), Crescenza (Gobbetti and others 1997), fresco cheese (Vinderola and others 2000),Árzúa-Ulloa (Menéndez and others 2000), cottage cheese (Blanchette and others 1996;Roy and others 1997;Vinderola and others 2000), white cheese (Kasımoglu and others 2004), and fresh cheeses (Roy and others 1997;others 2005a, 2005b). Most of the cheeses tested succeeded in maintaining the viability of these microorganisms.…”
Section: Introductionmentioning
confidence: 99%
“…2), and paired t tests showed this difference was statistically significant (P=0.03). A previous study had also shown that cells added at salting were stable during storage (Dinakar and Mistry 1994), but no comparison with other points of inoculation had unfortunately been carried out.…”
Section: Viable Counts During Storagementioning
confidence: 99%
“…In cottage cheese, it was suggested to add the probiotic culture in the cream dressing rather than in the curds (Blanchette et al 1996). Other studies have examined inoculation at the cheddaring step or at salting (Dinakar and Mistry 1994;Fortin et al 2011;Gomes da Cruz et al 2009). With free cells, these inoculation practices raise the concern of cell losses in whey.…”
Section: Viability Of Bifidobacterium Longum In Cheddar Cheesementioning
confidence: 99%